2011
DOI: 10.1371/journal.pone.0025851
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Triacylglycerol Biosynthetic Pathways via De Novo Transcriptomic and Proteomic Analyses in an Unsequenced Microalga

Abstract: Biofuels derived from algal lipids represent an opportunity to dramatically impact the global energy demand for transportation fuels. Systems biology analyses of oleaginous algae could greatly accelerate the commercialization of algal-derived biofuels by elucidating the key components involved in lipid productivity and leading to the initiation of hypothesis-driven strain-improvement strategies. However, higher-level systems biology analyses, such as transcriptomics and proteomics, are highly dependent upon av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
150
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(166 citation statements)
references
References 51 publications
9
150
1
2
Order By: Relevance
“…M8, particularly for DGAT that exhibited reduced expression during nitrogen-starvation. Post-transcriptional control of DGAT has been reported in proteomics studies of Chlorella vulgaris (Guarnieri et al, 2011) and Brassica napus (Nykiforuk et al, 2002), and has also been suggested for Neochloris oleoabundans (Rismani-Yazdi et al, 2012). The evidence for posttranscriptional control of DGAT is further supported by the lack of the phospholipid:diacylglycerol acyltransferase (PDAT) gene within the Tetraselmis sp.…”
Section: High Lipid Accumulation During Stationary Phase Of Tetraselmmentioning
confidence: 88%
See 1 more Smart Citation
“…M8, particularly for DGAT that exhibited reduced expression during nitrogen-starvation. Post-transcriptional control of DGAT has been reported in proteomics studies of Chlorella vulgaris (Guarnieri et al, 2011) and Brassica napus (Nykiforuk et al, 2002), and has also been suggested for Neochloris oleoabundans (Rismani-Yazdi et al, 2012). The evidence for posttranscriptional control of DGAT is further supported by the lack of the phospholipid:diacylglycerol acyltransferase (PDAT) gene within the Tetraselmis sp.…”
Section: High Lipid Accumulation During Stationary Phase Of Tetraselmmentioning
confidence: 88%
“…Currently, algal strain development remains one of the most important aspects of microalgae-for-biofuel Sun et al, 2013). In most studies, the focus has been on metabolic pathway reconstruction and gene discovery at a single time-point, usually 48 to 96 h into starvation phase when lipid accumulation is at its peak (Guarnieri et al, 2011; Rismani-Yazdi et al, 2012; Sun et al, 2013). While this approach successfully allowed for the reconstruction of fatty acid (FA), triacylglyceride (TAG), β-oxidation and other metabolic pathways, the limited scope of these studies restricts our understanding how the expression of these pathways change, particularly during early stationary phase as cells transition from growth phase into starvation phase.…”
Section: Introductionmentioning
confidence: 99%
“…The lipids produced by C. vulgaris can be grouped in the esters: triacylglycerol (TAG), phosphatidylglycerol (PG), phosphatidylinositol (PI), phosphatidylethanolamine (PE), sulfoquinovosyldiglycerol, monogalactosyldiglycerol (MGDG), digalactosyldiglycerol, and phosphatidylcholine, where TAG can accumulate to 20% to 60% of dry cell weight (Guarnieri et al, 2011(Guarnieri et al, , 2013Bellou et al, 2014).…”
Section: Defining the Biomass Objective Functionmentioning
confidence: 99%
“…RNA sequencing data and literature data such as specific CO 2 and Glc consumption rates were used to constrain the model under growth conditions in the light and dark (Guarnieri et al, 2011). For each growth condition, the storage and consumption of starch were taken into account; we calculated the rates using experimental data (Supplemental Table S6).…”
Section: Constraints and Growth Simulationsmentioning
confidence: 99%
See 1 more Smart Citation